Detecção do limiar de lactato salivar e da variabilidade da freqüência cardíaca em exercício resistido: comparação entre métodos - Oliveira, João Carlos de (Universidade Federal de São Carlos, 2007)
Important researches had shown the benefits of resistance training programs for rehabilitation as well as prophylaxis of physical incapacity. However few studies had investigated the responses of the intermediate metabolism during the execution of resistance exercises if carried through steady state or during incremental tests. The purpose of this study was to investigate the viability of the use of non-invasive methods as trustworthy indicators in the analysis of the aerobic-anaerobic transition and to compare the physiological responses between male and female, submitted to discontinuous incremental test of resistance exercise for lower limb. Eighteen subjects volunteered to participate and provided a written consent (9 males, 24 ± 3 years, 176 ± 5 cm, 72 ± 10 kg and 9 females, 23 ± 2 years, 165 ± 6 cm, 59 ± 10 Kg) in two sessions, distinct days, of counterweighted isoinertial Leg Press 45º machine (LP), being the 1st session performed to identify the 1 repetition maximum load (1RM) and the 2nd to accomplish the discontinuous incremental test of the type step in LP (DIT). The loading gradual scheme was determined in relation to the percentage of 1RM (%1RM). Subjects were required to perform 20 ± 2 repetitions with a 2 minutes interval between each set when loads were changed and collection of blood and salivary samples were collected. The blood lactate concentration ([La-]) had been used as gold standard for the respective comparisons between the methods. As non-invasive methods the salivary lactate concentrations ([SL]) and index SD1 of the heart rate variability (HRV) were used, gotten by Poincaré Plotting (PP). The thresholds identified by [La-] and [SL] (LT and SLT, respectively) had been determined by Mader and Heck Method (1986). The threshold identified by index SD1 (SD1T) was determined by Tullpo et al. (1998) criterion. The criterion level for statistical significance was set at an alpha level of p< 0,05. Statistical differences had not been found in the comparisons between genders in each step of the DIT for the three variables studied. The thresholds when expressed in kg revealed significant differences between genders but not intra genders. When expressed in %1RM the thresholds had been placed in the average enter 29-40% and had not evidenced significant differences between the thresholds in the conditions intra genders and between genders. Correlations of 0.89 and 0.78 had been evidenced between the LT and SLT and SD1T, respectively. The variability of both non-invasive variables was shown inside of the limits of agreement evidenced by the analyses of Bland-Altman. Thus it is possible to conclude that as much the SL as index SD1 of HRV responses of similar form to the blood lactate. This allows the detention of the thresholds of lactate salivary and heart rate variability, independently of the gender. In this way, as much the SL as index SD1 of the HRV presents great potential as possible non invasive markers of effort intensity, that they can be used in the lapsing and the control of the load of work in the resistance exercises. Moreover, the differences in the metabolic responses between the genders, evidenced in the intensities of effort above of the threshold, must be considered in the lapsing of the resistance training.
Keywords: Identidade de Gênero; Limiar anaeróbio; Lactato salivar; Variabilidade da freqüência cardíaca; Equipamento Leg Press; Gender differences; Anaerobic threshold; Blood lactate; Salivary lactate; Leg Press; CIENCIAS BIOLOGICAS::FISIOLOGIA